Community Participation in Household Waste Management as a Medium for Environmental Education: A Descriptive Qualitative Study in Badung Regency - Shinta Enggar Maharani; I Nyoman Arya Thanaya; Made Sudiana Mahendra; I Gusti Bagus Sila Dharma (Jurnal Pendidikan Biologi Undiksha, 2025)
Household waste management is not only a technical matter but also a reflection of community awareness and environmental values. This study aims to explore the forms, motivations, and educational potential of community participation in household waste management in Badung Regency, Bali. Using a descriptive qualitative design, data were obtained through in-depth interviews, participatory observation, and documentation of local waste management initiatives such as waste banks and neighbourhoods composting groups. The results reveal that community involvement emerges from collective environmental concern, local cultural norms, and the desire to maintain cleanliness and harmony (Tri Hita Karana principles). Participation in waste segregation, recycling, and composting serves as an informal yet powerful medium for environmental education, where residents, including students, learn ecological concepts through practical experience. Community-based programs have strengthened eco-literacy, social responsibility, and sustainable behaviours among participants. The study concludes that integrating education with community-driven waste management can create transformative learning that bridges everyday practice with environmental awareness. This integrative model offers insights for educators and policymakers who will implement continuing education through local participation